In Vitro Determination of Antioxidant activity, total phenolics, total flavonoids, anti-cholesterol of extracts Saffron (Crocus sativus) - Muhammad Ryan Radix Rahardhian (Journal of Global Pharma Technology, 2020)
Background: In Indonesia, saffron (Crocus sativus) drinks are now the latest healthy lifestyle trend. Saffron is used as a natural antioxidant, where antioxidants are related to cholesterol inhibition. The antioxidant activity of saffron is closely related to the content of flavonoids and phenolic compounds. This study aimed to determine Saffron 50% ethanol extract's effect on antioxidant activity, total phenolic content (TPC), total flavonoid content (TFC), and anti-cholesterol. Methods: Inhibition of antioxidant activity with 2-diphenyl-1-picrylhydrazyl DPPH, determining TPC using Folin-Ciocalteu and TFC reagent using AlCl3 reagent, and anti-cholesterol with Cholesterol Standard. Results: TFC 19.14 ± 0.9 mg QE / g, TPC 4.8 ± 0.9 mg GAE / g, antioxidant activity with extract IC 50 6939.02, Quercetin 9.57, Rutin 41.70, and decreased the greatest cholesterol occurred at a concentration of 400 ppm with a decrease of 13.22%. Conclusion: The 50% saffron ethanol extract can be an antioxidant and anti-cholesterol in vitro, but it needs further testing in vivo with the same extract.